Professional Counselor; Is the new normal period ready for guidance and counseling services? - Muthmainnah Muthmainnah (Universitas Muhammadiyah Enrekang, 2021)
Since December 2019, the COVID-19 pandemic has wreaked havoc on people's lives, particularly in the field of education. Work from home (WFH) and children learning through virtual tools are putting pressure on people all over the world to become accustomed to digital technology including internet connections. Furthermore, the COVID-19 pandemic has caused modifications in daily educational activities that students engage on a regular basis, the first is the pattern of interpersonal interaction. Changes occur unexpectedly make it increasingly challenging for learners to adjust since they are unfamiliar with the circumstances. The implementation of the whole new lifestyle, obviously, necessitates a high level of student adaptability. Learners are, certainly, able to adjust to diverse situations and conditions in accordance with the human concept of an adaptable mechanism. It was only that there are a variety of different challenges that students should overcome in order to improve their adaptation. The role of counselor as professional aid services in Guidance and Counseling for students is extremely significant in this implementation of study, considering the prevailing new normal situations.